Study of Ponds in Kathmandu Valley and Analysis of their Present Situation - Adhikari, Bikash; Parajuli, Anmol; Adhikari, Prakash (Historical Journal, 2020)
Ponds in Kathmandu were constructed to feed the sub surface aquifers of stone spouts and dug wells at all seasons. The study focuses on how the ponds have been saved, reduced in size or completely lost. The causes behind the degradation of ponds are forces of intervention and disturbances that lead to the loss of the originality, quality and quantity of ponds throughout its timeline. Out of eight existing ponds in the study area, 10 samples were taken from eight different ponds for quality assessment. The historical significances and status, uses as of 2019 are tabulated based on field survey. The paper focuses on the study of pH, Total Solids, Electrical Conductivity, Ammonia, Nitrate, Phosphate, Ammonia, Dissolved Oxygen, Biological Oxygen Demand, Total Organic Matter, Chlorophyll, E. Coli, and dimensions of existing ponds. The physical, social stresses and lack of regular inspection of ponds have contributed to their degradation. However, the existing ponds require sustainable management. Proper safeguarding mechanism should be developed for the regular aeration of water in the ponds such as fountains so that the ponds have more dissolved oxygen eliminating faulty smell and control fish death.